2022
DOI: 10.1097/rlu.0000000000004007
|View full text |Cite
|
Sign up to set email alerts
|

Angiofibroma of Soft Tissue on MRI and FDG PET/CT Image

Abstract: Angiofibroma of soft tissue is a rare benign mesenchymal neoplasm. We reported a case of angiofibroma of soft tissue in a 61-year-old woman. MRI examination indicated a soft tissue mass in the right lower thigh, which showed isosignal intensity on T1-weighted imaging and heterogeneous high signal intensity on T2-weighted imaging. This lesion had intense tracer uptake, with an SUV max of 7.24 on FDG PET/CT. Our case revealed that when soft tissue masses with intense FDG uptake on PET/ CT are encountered, angiof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To date, fewer than 100 cases of AFST have been reported in the English literature, 1,3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and the clinicopathological, immunohistochemical, and genetic features of AFST still remain not fully understood. In studies including more than 10 cases of AFST, this is the first report that identified driver fusion genes in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…To date, fewer than 100 cases of AFST have been reported in the English literature, 1,3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and the clinicopathological, immunohistochemical, and genetic features of AFST still remain not fully understood. In studies including more than 10 cases of AFST, this is the first report that identified driver fusion genes in all cases.…”
Section: Introductionmentioning
confidence: 99%